Solitary nasopharynx metastasis from hepatocellular carcinoma after liver transplantation: A case report. Issue 7 (February 2019) - Lou, Li-Li; Zhang, Ying; Huang, Xu; Zhang, Li-Xia; Ji, Hui-Fan; Li, Xu; Guo, Xiao-Lin
Abstract: Rationale: Hepatocellular carcinoma (HCC) is the fifth most common cancer and third leading cause of cancer-related deaths worldwide. Nasopharyngeal metastasis of hepatocellular carcinoma is very rare. This is the first report of posttransplantation nasopharyngeal metastasis. Patient concerns: A 45-year-old man with a history of hepatitis B related hepatocellular carcinoma (HCC) in the right segment of the liver received an orthotopic liver transplant. Two year after the transplantation, he suffered from severe headache, and head contrast enhanced CT scans did not show clues for brain or skull metastasis. Then he developed hoarseness and dysphagia. Diagnosis: The nasopharyngeal cancer was confirmed to be metastatic tumor from liver histologically according to biopsy. Interventions: This patient underwent radiotherapy (RT) of the metastatic nasopharyngeal tumor, and there was significant symptomatic relief. Outcomes: The patient died 3 months after nasopharyngeal metastasis was diagnosed. Lessons: Recurrence of hepatocellular carcinoma with metastasis of nasopharyngeal carcinoma after liver transplantation is rare, but the prognosis is very poor. Close follow-up of patients should be paid attention to prevent the occurrence of such diseases.